2019
DOI: 10.17049/ataunihem.547213
|View full text |Cite
|
Sign up to set email alerts
|

Hiperemezis Gravidarum Tanısı Alan Gebelerin Gebeliğe Uyum ve Stresle Başa Çıkma Tarzlarının Belirlenmesi

Abstract: This research has been done in order to determine of adapting to pregnancy and coping styles with stress of pregnant diagnosed of hyperemesis gravidarum. Methods: The descriptive study was conducted with 160 pregnant women diagnosed as hyperemesis gravidarum and hospitalized in a women's health education and research hospital. Ethics Committee approval and the necessary permits are obtained for this research. Information Form, Prenatal Self Evaluation Questionnaire (PSEQ) and Ways of Coping with Stress Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, the mean FC score of the pregnant women was found to be 26.53 ± 5.68. In studies using the same scale, the mean FC scores of healthy pregnant women ranged from 20 to 29 (2,24,25), while the mean total FC scores of high-risk pregnant women ranged from 22 to 28 (21,22,25,26). In their study, Mete et al (18) found the mean FC score as 24.24 ± 6.09 before the childbirth birth preparation training and 23.10 ± 8.80 after the training.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the mean FC score of the pregnant women was found to be 26.53 ± 5.68. In studies using the same scale, the mean FC scores of healthy pregnant women ranged from 20 to 29 (2,24,25), while the mean total FC scores of high-risk pregnant women ranged from 22 to 28 (21,22,25,26). In their study, Mete et al (18) found the mean FC score as 24.24 ± 6.09 before the childbirth birth preparation training and 23.10 ± 8.80 after the training.…”
Section: Discussionmentioning
confidence: 93%
“…During the first half of women's pregnancy, hospitalization is required for those who suffer nausea and vomiting; nevertheless, the cause of this phenomenon is still unknown (London et al, 2017). Even so, a large number of studies have delved into the emotional impact of a Hyperemesis Gravidarum among early pregnancies (Bulin, 2019;Bulut & Özdemir, 2019;Khoramroudi, 2018;Mekonnen et al, 2018). Among patients in HG, anxiety and emotional distress were more prevalent and severe (Hussien et al, 2019).…”
Section: Introductionmentioning
confidence: 99%